Comparative assessment of respiratory and other occupational health effects among elementary workers. Issue 3 (3rd July 2019) - Hamid, Almas; Saleem, Wajeeha; Yaqub, Ghazala; Ghauri, Moin ud din
Abstract : Objective . This study was conducted to assess hazards faced by elementary workers. Methods . A questionnaire survey and a respiratory function test (spirometry) were carried out on 150 respondents. Results . Major hazards identified related to sharp objects, heavy weight lifting, thermally harsh conditions, working at height, whole body vibration, chemicals, pathogens, increased noise levels and confined space entry. Workers suffered from upper and lower respiratory disorder symptoms, digestive problems, optical and musculoskeletal issues, etc. Spirometric measurement showed obstructive lung disorders to be highest among construction workers (CW) (48%) followed by sanitation workers (SW) (32%) and solid waste pickers (SWP) (28%). Restrictive lung pattern was dominant among SW (56%) followed by SWP (46%) and CW (42%). The observed FEV1 /FVC in diseased SWP, SW and CW ranged from 51 to 96%, from 52 to 98% and from 31 to 99% respectively while observed mean FEV1 was 2.15, 1.79 and 1.70 L, respectively. Conclusion . The study findings show that occupational exposure can significantly influence respiratory system impairment and contribute to other ailments among elementary workers. The study recommends use of appropriate protective equipment and regular medical examination for early recognition of any health risk so that timely interventions for effective management may be undertaken.